Healthy Food Creation Training: A Solution To Prevent Stunting For Mothers And Children At Community Health Center In Cimahi Tengah - Ita karnita; Sara Rabasari; Surya Aditya Wahyono; Ghini Khuntala Devi; Tina Andriana Suhada (Inaba of Community Services Journal, 2024)
This community partnership program focuses on supporting the Cimahi Tengah Health Center team by providing input on managing and creating healthy food products. It aligns with the government's broader strategy to reduce stunting in Indonesia by promoting the use of local ingredients in nutritious recipes. In collaboration with the Cimahi Tengah Health Center and Akademi Pariwisata NHI Bandung, the program emphasized the importance of local food resources in combating nutritional deficiencies. By focusing on sustainability and community engagement, the training targeted health professionals, equipping them with the skills to create nutritious, anti-stunting meals that appeal to children and promote healthy eating habits from an early age. The primary purpose of the program was to bridge the gap between nutritional knowledge and its practical application by teaching innovative food processing techniques. It aims to empower health professionals with the tools to create meals that are both nutritious and visually appealing, making them attractive to children. By promoting the use of local ingredients, the program also sought to enhance the value of local commodities while addressing the root causes of malnutrition and stunting. The program achieved all its objectives, with 100% of its goals met. The collaboration between the Cimahi Tengah Health Center and AKADEMI PARIWISATA NHI Bandung played a crucial role in its success, Participants learned hands-on techniques for creating nutritious meals using local ingredients and strategies to encourage children to adopt healthier dietary habits. This initiative not only addressed immediate nutritional needs but also laid the groundwork for long-term health improvements.